Pancreatic Neuroendocrine Tumors: Does Chemotherapy Work? - Tejani, Mohamedtaki Abdulaziz; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2014)
Pancreatic neuroendocrine tumors (pNETs) are rare well-differentiated neoplasms which can be functional or non-functional. They tend to have a worse prognosis than their counterpart carcinoid tumors. Current systemic treatment options for advanced, unresectable disease include somatostatin analogs, everolimus and sunitinib. Low response rates and toxicity profiles have, thus far, limited the widespread use of cytotoxic chemotherapy in this setting. In this update, we review three abstracts from the 2014 ASCO Gastrointestinal Cancers Symposium that present outcomes of the use of combination capecitabine and temozolomide in patients with advanced pNET. We summarize their results and discuss the role of this regimen in treatment algorithms for metastatic pNET. Image: University of Rochester logo